Diagnosis of Bernard Soulier Syndrome and Glanzmann’s Thrombasthenia in Iraqi Patients - Lina Mussa Kadhim; Muthana Ibrahim Malak; Safa A Faraj (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Bernard–Soulier syndrome (BSS) and Glanzmann Thrombasthenia (GT) are rare inheritedplatelet function disorders, defined by a permanent history of mucocutaneous bleeding. The objective of thisproject was to identify biological and clinical characteristics of BSS and GT patients. Methodology: Thisstudy included 52 patients with bleeding disorders, the clinical, haematological and demographic featuresof patients were determined and the level of GpIIb/IIIa and GPIb/IX was assessed. Results: From a total of52 patient, 20 were diagnosis with BSS (9 females and 11 males), their age range from 6 to 42 year and 23diagnoses with GT (10 females and 13 males), their age range from 4 to 50 year. Epistaxis, easy bruising,menorrhagia and ecchymosis were the most frequent symptoms. Prolonged bleeding time (BT), normal PTand PTT were seen in all cases. Variable thrombocytopenia, large platelets with decreased GPIb/IX levelwere seen in BSS patients, while the level of GPIIb/IIIa was decreased in GT cases. Conclusion: SinceBSS and GT are infrequent disorders diagnosis may be postponed, both diseases are combined with crucialbleeding tendency, therefore earlier detection would have been important for patients management.